UNDERSTANDING THE SUCCESS CHARACTERISTICS ON LIVE-STREAMING TOWARDS PURCHASE INTENTION IN INDONESIA - Yusrin, Nur Amalyna (Universitas Multimedia Nusantara, 2024)
Abstract- The rapid growth of social commerce and the integration of social media features into e-commerce are the basic factors required for every e-commerce monitoring application. This research aims to determine the characteristic factors of streamers that contribute to purchase intentions in the live streaming shopping environment in Indonesia, which consist of personality traits, professionalism, and social affordability. The novelty of this journal lies in its comprehensive analysis of the specific characteristics of streamers and their influence on consumer behavior in the context of live-streaming shopping. This unique combination of personality traits, professionalism, and social affordance has not been widely studied in the context of livestream shopping, making this research a pioneering effort in this area. The research methodology uses a quantitative approach, using survey data collection, descriptive statistics, and multivariate tests to analyze hypotheses. This research collected and analyzed data from 302 respondents in the Jabodetabek area, using non-probability cluster sampling to ensure a representative sample. Empirical findings show that personality traits and social skills of streamers have a significant positive influence on viewers' purchase intentions in the context of live streaming shopping in Indonesia. In conclusion, this research emphasizes the importance of streamer characteristics in influencing viewers' purchasing intentions in live-streaming shopping. The implications of this research highlight the need for streamers to focus on developing specific traits to increase audience engagement and drive purchase intent, which will ultimately contribute to the growth of social commerce in Indonesia. Keywords: Live Streaming; Profesionalisme; Purchase Intention; Personality Traits; Social Affordance